Development, reliability and validity of the Closed Kinetic Chain Lower Extremity Stability Test (CKCLEST): a new clinical performance test - Arikan, H.; Maras, G.; Akaras, E.; Citaker, S.; Kafa, N. (Research in Sports Medicine, 2022)
This study aimed to develop and determine the test-retest, intra- and interrater reliability, and validity of the Closed Kinetic Chain Lower Extremity Stability Test (CKCLEST). Three-blinded, cross-sectional, repeated-measures clinical measurement reliability trial. Fifty young adults participated in this study. To assess the reliability of CKCLEST, intraclass correlation coefficient, standard error of measurement, minimal detectable change, and Bland-Altman plot were used. For concurrent validity of CKCLEST was applied Spearman correlation analysis with Vertical Jump Test, Isokinetic Dynamometer Test, Single-Leg Hop Test, and Prone Bridge Test. All analyses were made for both the best score and the average score. CKCLEST showed excellent reliability. ICC for test-retest reliability (0.93; 0.84), intrarater reliability (rater 1: 0.90; 0.83- rater 2: 0.93; 0.85), and interrater reliability (0.90; 0.83) was calculated for average score and best score, respectively. CKCLEST was found to be moderately correlated with each of the tests. CKCLEST is a highly reliable, valid, and new clinical assessment tool.